Analisis Sebaran Kebakaran Lahan Kota Pekanbaru Terhadap Perubahan Iklim - Keke Nur Aini; Aryo Sasmita; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Climate change is a phenomenon that occurs not only due to nature, but also from the intervention of human actions. Climate change will caused vulnerability in an area due to changes in environmental conditions on physical, chemical and biological. The purpose of this study was to find out how the spread of land fire disasters in the City of Pekanbaru to climate change so that mitigation and adaptation measures can be taken in Pekanbaru City. The results of the study found that the sub-district that occurred in the field of fire was Payung Sekaki, while the sub-district which occurred in the field of fire was Pekanbaru City and Senapelan.Keyword: climate change, field of fire, mitigation-adaption, vulnerability